The afterlife of enclosure - Lesjak, Carolyn (Stanford University Press, 2021)
Introduction : realism and the commons – The persistence of the commons, the persistence of enclosure – Dickensian types and a culture of the commons – Eliot, cosmopolitanism, and the commons – The typical and the tragic in Hardy's geopolitical commons – Afterword : old and new enclosures
Includes bibliographical references and index
Keywords: Dickens; Charles; Eliot; George; Hardy; Thomas; English fiction; Commons in literature; Inclosures in literature; Working class in literature; Realism in literature; Criticism; interpretation; etc